"Always Thinking About Safety": African American Lesbian Mothers' Perceptions of Risk and Well‐being. Issue 3 (16th October 2020) - Radis, Brie; Nadan, Yochay
Abstract : Although there is a growing body of knowledge focusing on lesbian families and their parenting experiences, African American lesbian mothers are often underrepresented in research. This qualitative exploratory study aims to understand the constructions and perspectives of African American lesbian mothers, from an urban East Coast area, on risk and well‐being. Fifteen in‐depth semi‐structured interviews were conducted and analyzed at the end of 2016, coinciding with the presidential election yielding main themes that were significant for the participants pertaining to the mothers' experiences and construction of the challenges and risks to well‐being. Main themes first focused on discrimination and insensitivity in everyday spaces; then moved into the effects of political climate on perceived safety and security, conditions and unintended consequences of the coming out process; and ended with strategies for reducing risk. Adoption of an intersectional framework to discuss our findings allowed us to explore the ways in which multiple identities engage to shape experiences and constructions of risk and well‐being among African American lesbian parents. The results suggest the importance of context (e.g., political, historical, gender‐related, racial) when working with LGBTQ+ families of color. Resumen: Aunque hay un corpus cada vez más extenso que se centra en las familias lesbianas y sus experiencias de crianza, las madres lesbianas afroamericanas generalmente están infrarrepresentadas en las investigaciones. Este estudio cualitativo exploratorio tiene como finalidad comprender las construcciones y las perspectivas sobre el riesgo y el bienestar de las madres lesbianas afroamericanas de un área urbana de la Costa Este. A finales de 2016, se llevaron a cabo y se analizaron quince entrevistas semiestructuradas detalladas que coincidieron con los temas principales generados por la elección presidencial y que eran significativos para las participantes en relación con las experiencias de las madres y la construcción de las dificultades y los riesgos para el bienestar. Los temas principales se centraron primero en la discriminación y la insensibilidad en los espacios cotidianos; luego pasaron a los efectos del clima político en la seguridad y la protección percibidas, las condiciones y las consecuencias involuntarias del proceso de salir del clóset; y terminó con estrategias para reducir el riesgo. La adopción de un marco interseccional para debatir nuestros resultados nos permitió analizar las maneras en las que interactúan las diferentes identidades para determinar las experiencias y las construcciones de riesgo y bienestar entre madres lesbianas afroamericanas. Los resultados indican la importancia del contexto (p. ej.: político, histórico, relacionado con el género, racial) a la hora de trabajar con familias de color LGBTQ+. 摘要: 虽然在女同性恋家庭和她们的养育经验方面已经有越来越多的了解，但针对美国女同性恋母亲的研究往往是不够代表性的。本研究是一项质性探索性研究，旨在了解来自东海岸城市地区的非裔美国女同性恋母亲对风险和福祉的理解和观点。2016年底，研究者对这个群体进行了15次半结构化的深度访谈，并对访谈内容进行了分析。研究进行时恰逢总统大选，这个背景产生了对受访者来说具有重要意义的主要主题，涉及母亲们对什么是幸福的挑战和对风险的体验和建构。分析得出的主题首先是关注日常空间中的歧视和不敏感; 其次的主题是关于政治气候对感知的安全和保障、出柜过程的条件和意外后果的影响；最后关于降低风险的战略。本研究采用交叉框架来讨论我们的发现，使我们能够探索非裔美国女同性恋父母以多重身份参与塑造经验的方式和影响构建风险和幸福的方式。研究结果显示，在与LGBTQ+ 有色人种家庭做研究项目时，背景因素(例如，政治、历史、性别相关、种族)起重要作用。